Spatio-temporal systems in Chaucer’s language: A discourse-pragmatic analysis - Minako Nakayasu (LingBaW)
The purpose of this paper is to conduct a discourse-pragmatic analysis of the spatio-temporal systems in Chaucer’s language along the lines of historical pragmatics and discourse analysis. The text used for analysis is “The knight’s tale” adopted from the Riverside edition of The Canterbury tales. Language has built-in spatio-temporal systems by which speakers judge how distant the situations they wish to express are from their domain, i.e. proximal or distal. Spatio-temporal elements can be connected to each other to take either a proximal or a distal perspective in discourse. Based on this approach, the present paper performs a detailed examination of the spatio-temporal elements, and addresses the following questions: 1) How does the perspective change as the discourse progresses? and 2) What factors are relevant to this change in discourse? To provide answers to these questions, this paper will investigate: 1) elements which structure discourse, 2) elements which promote a proximal or a distal perspective, 3) elements which trigger alternations of these perspectives, and 4) factors which facilitate the alternation of elements in either the spatial, the temporal, or the integrated spatio-temporal domain.